Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c8pp00223a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of experimental light activated gels for tooth bleaching

Abstract: Gels containing TiO2/Ag or TiO2 particles are less cytotoxic than hydrogen peroxide-containing gels. TiO2/Ag gel exhibited a stronger reduction of metabolic activity and viability than TiO2 gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…They observed that diluted gel formulations tested against L-929 cells, 3T3 cells, and gingival fibroblasts did not reveal any noticeable reduction in cell viability. The authors suggested additional experiments aiming to assess the TiO 2 gel toxicity [92]. Sodagar et al solved the problem of caries next to brackets in orthodontic treatment.…”
Section: Other Applications Of Tio 2 Nanoparticles In Medicinementioning
confidence: 99%
“…They observed that diluted gel formulations tested against L-929 cells, 3T3 cells, and gingival fibroblasts did not reveal any noticeable reduction in cell viability. The authors suggested additional experiments aiming to assess the TiO 2 gel toxicity [92]. Sodagar et al solved the problem of caries next to brackets in orthodontic treatment.…”
Section: Other Applications Of Tio 2 Nanoparticles In Medicinementioning
confidence: 99%
“…Thus, a low-concentration bleaching agent group has been introduced, where the effect of peroxide is catalyzed and strengthened by an agent such as TiO 2 , which produces free radicals such as vital oxygen and hydroxyl when exposed to light. 31 Furthermore, Kurzman et al 32 reported that experimental bleaching gels containing TiO 2 had lower cytotoxicity than gels containing only HP. The use of TiO 2 as a semiconductor and photocatalytic agent requires the use of UV light (<380 nm).…”
Section: Discussionmentioning
confidence: 99%
“…Medical/biological use [96] TiO2 (anatase, 25 nm) TiO2/Ag NPs commercial distribution of TiO2 anatase powder was mixed with silver nitrate, reduced and heated at 300 °C toxicity reduction of teeth whitening gels [97] TiO2 (anatase, ≤ 15μm) Eggshell-TiO2 composite (irregular, spherical shape particles, ≤ 13 nm)…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…They observed that diluted gel formulations tested against L-929 cells, 3T3 cells, and gingival fibroblasts did not reveal any noticeable reduction in cells viability. The authors suggested additional experiments aiming to assess the TiO2 gels toxicity [96]. Sodagar et al solved the problem of caries next to brackets in orthodontic treatment.…”
Section: Methods Of Synthesismentioning
confidence: 99%